MEMBANGUN TEORI MAKROEKONOMI ISLAM YANG BERKEADILAN: ANALISIS PRINSIP ANTI RIBA DALAM QS. AL-BAQARAH 278-279 SEBAGAI FONDASI SISTEM EKONOMI SYARIAH - Saefullah, Achmad Fikri (Program Studi Ilmu Al-Qur’an dan Tafsir, Fakultas Ushuluddin, Universitas Annuqayah (UA), 2025)
Islamic Macroeconomics aims to realize an economic system that is just, sustainable, and in accordance with sharia principles. One of its main foundations is the prohibition of usury as emphasized in Surah Al-Baqarah verses 278–279, which not only strictly prohibits the practice of usury but also warns of the spiritual and social consequences for violators. This paper uses a normative and analytical approach by examining sharia sources and Islamic economic literature to examine how anti-usury principles can form a theoretical framework for Islamic macroeconomics that is different from the conventional capitalist system. This article refers to several sources such as books and journals that discuss usury, interest, and just sharia economics. Beside that, additional references was obtained through interviews with economics students who were considered competent in usury matters. The focus of the study includes the influence of the prohibition of usury on economic stability, wealth distribution, and economic justice. In addition, this paper highlights the role of sharia instruments such as zakat, alms, and real sector investment as fair and inclusive alternatives. The results of the analysis show that the application of the anti-riba principle has the potential to create a more humane economic system and is oriented towards collective welfare. Thus, the verses of the Qur'an not only have spiritual value, but can also be a normative basis in building a fair and applicable macroeconomic theory.